Analisis Perilaku Sosial Ekonomi Jama’ah Pasca Umroh di Desa Pasar Bantal Kecamatan Teramang Jaya Kabupaten Muko-Muko - Salma Dia Winanta; Eka Sri Wahyuni; Kustin Hartini (Universitas Muhammadiyah Surabaya, 2026)
This study aims to identify and analyze the socio-economic behavior of pilgrims after performing Umrah in Pasar Bantal Village, Teramang Jaya District, Muko-Muko Regency, as well as the factors influencing it. This research used a qualitative method with a phenomenological approach to understand the experiences and behavioral changes of pilgrims after performing Umrah. Data collection techniques were carried out through in-depth interviews, observations, and documentation involving people who had performed Umrah. The results of the study indicate that Umrah worship has an influence on changes in the socio-economic behavior of pilgrims, such as increased religious activities, social awareness, charitable behavior, and a simpler lifestyle with greater caution in earning a livelihood. However, these changes did not occur evenly among all pilgrims because they were influenced by internal and external factors, such as the level of religiosity, personal motivation, economic conditions, and social environment. Thus, the spiritual experience during Umrah has an influence on the socio-economic behavioral changes of pilgrims in their daily lives.